2003
DOI: 10.1046/j.1471-4159.2003.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between myelin production and dopamine synthesis in the PKU mouse brain

Abstract: Phenylketonuria is caused by specific mutations in the phenylalanine hydroxylase gene and is characterized by elevated blood phenylalanine levels, hypomyelination in forebrain structures, reduced dopamine levels, and cognitive difficulties. To determine whether brain tyrosine levels and/or myelination play a role in the up-regulation of dopamine, phenylketonuric mice were placed on a low phenylalanine diet for 4 weeks and as blood phenylalanine levels dropped to normal, the relationships between phenylalanine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 46 publications
2
58
1
2
Order By: Relevance
“…In the prefrontal cortex, nucleus accumbens, and caudate putamen, there was also a marked reduction of DA release. Joseph and Dyer (9) showed that by placing the PKU mice on a low-Phe diet, DA and myelin basic protein were increased to near-normal levels in the striatum and frontal cortex, indicating a positive relationship between myelination and DA production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the prefrontal cortex, nucleus accumbens, and caudate putamen, there was also a marked reduction of DA release. Joseph and Dyer (9) showed that by placing the PKU mice on a low-Phe diet, DA and myelin basic protein were increased to near-normal levels in the striatum and frontal cortex, indicating a positive relationship between myelination and DA production.…”
mentioning
confidence: 99%
“…These results concur with our observations that there were no detectable histologic changes in these specific regions, although we did identify morphologic and immunohistochemical changes in the hypothalamus and mesencephalon. In addition, Joseph and Dyer (9) reported that when they used Luxol fast blue, a myelin-specific stain, there clearly was an increase in the amount of myelin in subcortical white matter, corpus callosum, and striatum of treated PKU mice compared with respective structures in untreated PKU mouse brain.…”
mentioning
confidence: 99%
“…Enfin, les dommages cérébraux peuvent aussi être causés par les anomalies de myélinisation et de démyélinisation. Ces anomalies sont apparemment le résultat de la combinaison d'une augmentation du turnover de la myéline et d'une réduction de sa production, qui sont des effets secondaires de l'augmentation de la Phe dans le cerveau [6,7] .…”
Section: Résuméunclassified
“…Otro importante mecanismo del daño cerebral en la FCU se atribuye a anomalías de la mielinización y la desmielinización. Estas anomalías son, por lo visto, el resultado de una combinación del incremento del recambio de mielina y la disminución de la producción de mielina, que son respuestas secundarias a un aumento de la phe cerebral [6,7] .…”
Section: Introductionunclassified